The Relationship Between Food Quality and Customers’ Loyalty in Miramar Restaurant Jakarta - Dendy Rosman; Wiranto Wiranto (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
Currently, an increasing number of new restaurants are being established in Jakarta. This resulted in increasing competition in the food and beverage business. To be able to survive in the intense business competition, restaurant managers must improve and improve the quality of food so that customers are more loyal. Therefore, the purpose of this study was to determine the effect of food quality on customer loyalty at Miramar Restaurant. This research used a descriptive quantitative method. The data analysis method used simple linear regression analysis with IBM SPSS 25. The sampling technique uses judgemental sampling and involves 100 restaurant customers who have visited the restaurant at least once. The results of data processing using simple regression analysis shows that food quality has a positive and significant influence on the level of customer loyalty. The magnitude of the effect of food quality on customer loyalty is 48.1%. The results of this research are expected to provide input for the management of Miramar Restaurant in particular, and other restaurants in general regarding the importance of maintaining and improving food quality. By paying special attention to food quality, it will increase customer loyalty.